True or false?: remarkable women. (Chicago, Illinois: Workbook, 2019)
Who was the first woman in space? Was Rosa Parks the first person to be arrested for resisting bus segregation? Who was the youngest to win the Nobel Peace Prize? World Book's True or False?: Remarkable Women is here with the answers to these questions and more! the True or False? series reveals the surprising truths behind common misconceptions and teaches the coolest facts about high-interest topics, from prehistoric people to fashion, sports, outlaws, ghosts, weird plants, and more! The engaging, play-along format makes learning exciting!